Review on the Socio-Economic Impacts of Trypanosomiasis - Kikwai, C.; Ngeiywa, M. (Africa Environmental Review Journal, 2022)
Trypanosomiasis is a parasitic disease that causes Animal African Trypanosomiasis, also known as nagana in animals and zoonotic Human African Trypanosomiasis, also referred to as sleeping sickness in humans. Tsetse flies are the primary vectors of African Trypanosomiasis, a disease of paramount importance to both humans and animals across the continent of Africa. The disease can also be mechanically transmitted by a number of biting dipteran flies such as Stomoxys calcitrus and Tabanus species. Tsetse fly occurs in 37 sub-Saharan countries covering nearly 10 million km2, an area approximately equivelent to one-third of Africa’s total land area. The fly and the disease occur in the world’s poorest countries with 32 out of the 37 affected countries being ranked the poorest in the world. In Kenya, approximately 138,000 km2 of land is tsetse infested with 38 out of the 47 counties being affected. Tsetse infested land coverage is roughly 25 percent of Kenya’s arable land, which limits livestock production and agricultural development affecting over 11 million Kenyans who are at risk of the disease. Tsetse infestation and trypanosomiasis infection have negative impacts on wildlife health and therefore affects tourism. In the past ten years, Human African Trypanosomiasis cases have been reported in tourists who had visited National Parks/Reserves and also among the local populations. Importation of costly drugs for treatment affects foreign exchange while the disease impacts on the country’s agriculture due to reduced milk and meat production, reduced live animal disposal value and reduced work efficiency of oxen used for cultivation. African Trypanosomiasis is considered the most important economically debilitating diseases which mostly contribute to poverty, hunger, and underdevelopment in the affected countries. Human infections affect labour resources and impacts negatively on school children performance which has an effect on their professional advancement later in life. In conclusion,African Trypanosomiasis poses serious threats to the lives and livelihoods of rural communities in Kenya. Therefore there is a priority need to control the disease to open up the affected underdeveloped areas to economic improvement and thus improve the lives of the residents.